Medición de la eficiencia en el uso de las regalías petróleras, una aplicación del análisis envolvente de datos (2012)
This paper evaluates and analyzes the relationship between royalty direct and the minimum coverage hit by oil-producing municipalities for the period 2007-2008, using the methodology of data envelopment analysis. This methodology has been implemented in different studies that evaluate the managing the transfers of exploitation oil. The results show an average pure technical efficiency of 24% for 2007 and 19,6% in 2008, in the four models analyzed, of which it is concluded that few municipalities with an efficient performance in terms of management of the royalties.